Desain Adjustable Spreader Bar Telescopic Menggunakan ANSYS - Wahyu Suryawan; Puji Basuki; Candra Wahyu S; January Jefry P; Muhammad Sagaf (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
This research aims to design an Adjustable Spreader Bar Telescopic that has high flexibility to adjust the needs of lifting loads in the long range of 3.48 meters to 4.27 meters. The design is carried out to provide solutions to the needs of the industry in lifting heavy loads with an optimal level of safety and efficiency. The research method involves several stages, starting from making geometric designs using CAD software, determining and entering the properties of the materials used, as well as modeling and simulation with the help of finite element analysis (FEA) software using ANSYS. The material used in this study is ASTM A992, which has high tensile strength and good deformation resistance. The simulation results show that the design of this telescopic bar spreader is able to withstand loads of up to 300 tons. In the simulation test, the minimum deformation was recorded at 0 meters, while the maximum deformation reached only 0.00031851 meters. The equivalent stress in the load has a minimum value of 9.7863 Pascal and a maximum of 3.1404 × 10⁸ Pascal. This value is still below the yield strength limit of ASTM A992 material, so the design is declared safe and feasible for application in the field. This research proves that the designed Adjustable Spreader Bar Telescopic is not only able to meet the needs of lifting loads with high capacity, but also has the flexibility of length that varies as needed. This advantage makes it an innovative solution for use in construction, logistics, and heavy industry projects that require lifting equipment with high performance and guaranteed safety.